ASSESSMENT OF GROUNDWATER MINERALIZATION IN THE AMU DARYA DELTA ON THE EXAMPLE OF THE XOJELI DISTRICT OF THE REPUBLIC OF KARAKALPAKSTAN - Aimbetov, I.; Dospanov, R. (SCIENCE and SOCIETY, 2024)
The article presents the results of studies of the hydrogeological conditions of the Xojeli district of the Republic of Karakalpakstan. Schematic maps of groundwater mineralization have been constructed. The results of studies on the salinity of groundwater in the Xojeli district of the Republic of Karakalpakstan showed that the mineralization of groundwater varies within 0.5-25 g/l. The lowest mineralization of groundwater is observed where the channels of the Amu Darya flowed. The groundwater of the studied area belongs mainly to sulfate (72%) and chloride-sulfate (22%) types of salinization. According to Shchukarev’s classification, groundwater mainly belongs to the sulfate and sulfate-chloride classes of salinity. To use the groundwater of the Xojeli district, it is necessary to purify the water from salts. The compiled schematic maps can be used in archaeological excavations of ancient cities and settlements of the Xojeli district.